Analgesic effects of piritramide in acute postoperative pain - comparison of intramuscular administration with patient-controlled intravenous analgesia and impact of OPRM1 and ABCB1 polymorphisms - Bartosova, Olga; Sima, Martin; Polanecky, Ondrej; Perlik, Frantisek; Adamek, Svatopluk; Lischke, Robert; Slanar, Ondrej (Biomedical papers, 2022)
Aims. The aim of this study was to compare the efficacy, consumption and safety after piritramide administered either intramuscularly (IM) on demand or via patient-controlled intravenous analgesia (PCA) and to examine the impact of OPRM1 and ABCB1 gene polymorphisms on the drug efficacy/safety in both regimens. Methods. One hundred and four patients scheduled for elective inguinal hernioplasty received piritramide with PCA or IM for postoperative pain management. We evaluated piritramide consumption, pain intensity using visual analogue scale (VAS) and adverse effects. Results. Median (IQR) piritramide consumption was 18.5 (13.5-31.2) and 15.0 (15.0-15.0) mg in the PCA and IM groups, respectively (P=0.0092). The respective values of area under the VAS2-16-time curve were 40 and 280 mm.h (P=0.0027). Opioid-induced adverse effects were more frequent in the PCA than in the IM group. Variant OPRM1 allele was associated with decreased pain relief, increased opioid consumption and increased incidence of adverse effects, while ABCB1 polymorphisms showed no impact on the observed parameters. Conclusions. We observed higher piritramide consumption, better pain relief and slightly worse safety profile in the PCA group compared with IM administration. Variant OPRM1 118G allele carriers required higher opioid dosing and suffered from more adverse effects, however, the differences between genotypes have been less pronounced in the PCA patients likely due to improved pain management via PCA.
Keywords: analgesia; opioid; piritramide; postoperative pain; adverse effects; gene polymorphism; intramuscular administration; patient-controlled intravenous analgesia